2023
DOI: 10.21203/rs.3.rs-2420890/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ambulance referral of more than 2 hours could result in a higher prevalence of medical- devices-related pressure injuries (MDRPIs) with different characteristics compared to the inpatient setting: A descriptive observational study

Abstract: Background Medical device-related pressure injuries(MDRPI) are prevalent and attracting more attention. During ambulance transfer, the shear force caused by braking and acceleration; extensive medical equipment crowed in a narrow space add external risk factors for MDRPIs. However, there is insufficient research on the relationship between MDRPIs and ambulance transfers. This study aims to clarify the prevalence and characteristics of MDRPI during ambulance transfer. Method A descriptive observational study wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…IHT poses a challenge in preventing PI, as patients are at a higher risk of developing PI due to prolonged inactivity or inadequate support surfaces during transport [10,11] . Our ndings indicated that both IHT and NT patients experienced a decrease in Braden scores during the rst four days.…”
Section: Discussionmentioning
confidence: 99%
“…IHT poses a challenge in preventing PI, as patients are at a higher risk of developing PI due to prolonged inactivity or inadequate support surfaces during transport [10,11] . Our ndings indicated that both IHT and NT patients experienced a decrease in Braden scores during the rst four days.…”
Section: Discussionmentioning
confidence: 99%